Numerical investigation on the aerodynamic resistances of double-unit trains with different gap lengths. Issue 1 (1st January 2021) - Li, Tian; Dai, Zhiyuan; Yu, Mengge; Zhang, Weihua
Abstract : Double-unit trains increase passenger capacity but also increase energy consumption. Therefore, research about the aerodynamic resistance of a double-unit train is of great importance to save energy. In this study, a commercial long-marshalling high-speed train and 8 kinds of double-unit trains are used to investigate the effect of the gap length on aerodynamic resistance. The results show that the aerodynamic resistance of the double-unit train is 8.5%-12.9% larger than that of the long-marshalling train. It is the tail car (CC1 car) of the first single-unit train and the head car (CC2 car) of the second single-unit train that lead to the difference in resistance. For the double-unit trains with different gap length, the resistance increases incrementally with the gap length, which is also mainly caused by the CC1 and CC2 cars. With increases to the gap length (starting from 0 mm), the resistance of the CC1 car increases with the cremental increases in the gap lengths. The resistance of the CC2 car also gradually increases when the gap lengths become larger. The resistance of the CC1 car with a gap length of 0 mm is slightly greater than that with 25 mm.